Influence of orifice nozzle geometry on flow and spray characteristics - Noor Azuani, Suliman (2013)
This thesis presented about the effects of nozzle orifice geometry on flow and spray characteristics. The thesis deals with the analysis on the different inlet diameter of nozzle orifice and the different inlet pressure on the flow and also spray characteristics. The objective of this thesis is to compare the final performance of flow and spray characteristics between the different designs of nozzle orifice. Besides that, the purpose of this thesis is to determine the flow and spray characteristics with different inlet diameter of nozzle orifice. This thesis also purposes to study the flow and spray characteristics with different inlet pressure. The geometry of nozzle orifice used is the inlet diameter and the parameter used is the pressure. The data used for analysis is obtained from the simulation by using Solidworks 2012 software. The post-processing method was performed using the simulation with certain parameters that can be chose and graph is plotted by using assistance software such as Microsoft Excel. From the result, it is observed that the performance of 150 µm diameter of nozzle orifice with inlet pressure of 250 bar is better than other combination of inlet diameter and inlet pressure. Future work, this comparison between different inlet diameter and different inlet pressure must do in experimental to support the result. There are many factors of geometry and parameters that required doing the comparison in order to study the flow and spray characteristics.